Question: Given that (alpha) and (beta) are roots of the quadratic equation 6x - 3x^2 = 4, find the equation whose roots are
square root (alpha) and square root (beta)
Sum of roots = 2
Product of roots = 4/3
How do I make it such that the sum of square root (alpha) and square root (beta) can substituted using the original sum of roots and product of roots to find it's value?
Sorry, i'm not sure of how to input the math signs
square root (a + b +2square root (ab))
= square root (2+2(4/3))
= square root (14/3)
= 2.160246899 on calculator
I think there's something wrong with the variables of the question, I haven't learn simple complex numbers or principal square roots.
I will check it out with my teacher, thanks for your help, you can mark this as solved now